Pengaruh Faktor Sosial Ekonomi terhadap Daya Saing Kelapa Sawit di Kabupaten Paser - Bustomi, Muhamad Yazid; Pratama, Adnan Putra; Sardianti, Andi Lelanovita; Abidin, Zainal; Prima, Doddy; Lisnawati, Andi; Putra, Pandhu Rochman Suosa; Barus, Mika Debora Br (Politeknik Negeri Lampung, 2023)
Many factors influence the development of oil palm, including socio-economic factors. Factors supporting success in oil palm cultivation must be considered as their contribution to the competitiveness of Indonesian palm oil to be accepted in export-destination countries. This study aims to determine the influence of socioeconomic factors on the competitiveness of oil palm. This research was conducted in Kertabumi Village, Kuaro District, Paser Regency, East Kalimantan Province. Data was collected in July-August 2023 with the questionnaires and interviews with respondents. Respondents in this study amounted to 65 farmers were determined using purposive sampling who members of the Bumi Subur cooperative in Kertabumi Village, Kuaro District, Paser Regency. The data analysis method uses the structural equation model-partial least square with the help of Smart-PLS software to find out what socio-economic factors affect the competitiveness of oil palm in Paser Regency, East Kalimantan Province. The results showed that the innovation factor of oil palm cultivation and the factor of production facilities had a positive and significant effect on the competitiveness of oil palm in Paser Regency, especially in Kuaro District, Kerta Bumi Village. This states that one way to improve the competitiveness of oil palm is to pay attention to the old factors of oil palm cultivation innovation, such as cultivating according to operational standards and environmentally friendly, to get an ISPO certificate. In addition, it is important to have complete production facilities by farmers to support oil palm cultivation and increase palm oil production.